Terasi Puger dan Kekuatan Kuliner Tradisional Dalam Perspektif Etnopedagogi - Alfira Intan Dwi Cahyani; Alfisyah Nurhayati; Kholis Alfin Mas Ula; M Ainur Rofiqi; Nada Febrianti Kusuma; Nivayatus Sayyadah; Ricca Rahim; Uswatun Hasanah (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This article aims to discuss the power of traditional culinary shrimp paste in an ethnopedagogical perspective and the process of shrimp paste production, and the people's reasons for shrimp paste production. The research method used is qualitative with a descriptive approach. The shrimp paste is produced using very traditional techniques and tools and utilizes existing Natural Resources (SDA), so that this Puger Terasi has a high taste and quality. In addition, the reason why people produce shrimp paste is because people work in the fisheries and marine products sector. The shrimp paste production process is carried out by the community in Puger to increase income and create jobs so as to reduce unemployment